Sustainable patient education in hidradenitis suppurativa - Elisabeth M. M. Christensen; Solveig Esmann; Ditte M. L. Saunte; Gregor B. E. Jemec (Wiley, 2023)
Abstract Background Hidradenitis suppurativa (HS) is a chronic inflammatory disease of recurrent painful nodules and sinus tracts mainly located in intertriginous skin areas. HS can cause physical and psychosocial impairments, and patients have a need for information and social support. Objectives An educational event was established to accommodate the aforementioned patient needs. The event presents updated information concerning HS and debates the lived experience of HS. This article outlines our approach to patient education. Methods The educational HS‐event has yearly welcomed patients and relatives at Roskilde hospital since 2010-except in year 2020 due to corona‐legislation. The educational content includes information on HS aetiology, epidemiology, treatment, psychosocial aspects of HS and current research. The team of educators is multidisciplinary and includes patients. Results Twelve thematic patient reported questions and concerns reoccur at the events. They include: The aetiology of HS and lifestyle, daily life, employment and economy, emotions, locations of lesions, heredity, comorbidities, self‐care to alleviate symptoms, treatment, the healthcare system, prognosis and new research. The participants are satisfied with the arrangement. Conclusion Educational activities such as the one outlined in this manuscript provides requested information, coping strategies social support. Studies are needed to investigate if systematic education of HS patients improves subjective and objectives measures. Plain abstract Patient education is an important part of disease management. It is essential to share different experiences and practices of patient education to optimize and inspire future educational programs. This study presents a decade of experiences from an annual event that has educated patients with the skin disease Hidradenitis suppurativa (HS). HS is a chronic inflammatory disease that causes skin abscess, nodules, and substantial scarring. The abscesses are extremely painful and located in areas of the body with skin‐to‐skin contact. Due to the painful condition the disease can cause both physical as well as psychological and social difficulties, and the patient group have a need for medical information and social support. In 2010 Roskilde hospital established an annual educational event for patients with HS and their relatives. The educational content includes general information regarding the disease, medical and surgical therapy options, psychosocial aspects of HS, and the latest scientific research concerning HS. The team of educators includes dermatologists, medical and PhD students, experts in psychology, representatives from the HS Patient Association and patients. In this study we outline our approach to patient education for those with HS and their relatives and present the participants' questions and comments as raised at these events. Arrangements such as this can be used to support the patients with the information needed to better understand their disease, but also to facilitate coping strategies and provide a framework for social support. Other studies are needed to investigate if education of patients with HS can improve subjective or objective measures.